Sharing and Control: The Janus-Faced Governance of Social Services at Times of Social Innovation and Social Investment - Lavinia Bifulco (Social Work and Society, 2020)
This paper focuses on Social Investment and Social Innovation, two crucial policy strategies within the current reorganization of European Welfare States. The aim is to illuminate the ambivalent dynamics of change, adaptation, and resistance that they unleash in the everyday governance of social services, especially regarding social citizenship and rights. The analysis is based on the empirical investigation of two cases in Italy: the implementation of an anti-poverty measure in Lombardy, a northern region of the country; and a project underway in Milan since 2015 aimed at reconfiguring the balance between supply and demand in care services within the context of a more comprehensive reorganization of local welfare systems. The two cases show different aspects of social services' governance, in particular concerning the coexistence of increasingly strict control mechanisms with the emphasis placed on principles of sharing and cooperation.